76.8k views
11 votes
What is the product of (4y - 5) (3y - 7)?

2 Answers

5 votes

Answer

(12y-35)

(4yx3y-5x7)

User MMakati
by
4.5k points
10 votes

Answer:

12y² - 43y + 35

Explanation:

Multiply each term of the first binomial by each term of the second binomial. Then combine like terms.

(4y - 5)(3y - 7) =

= 4y × 3y + 4y × (-7) + (-5) × 3y + (-5) × (-7)

= 12y² - 28y - 15y + 35

= 12y² - 43y + 35

User Kmmndr
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.